Enriching and enhancing digital cultural heritage through crowd contribution. Issue 1 (6th February 2017) - Gupta, Dinesh K.; Sharma, Veerbala
Abstract : Purpose: The purpose of this paper is to identify the status of digitization of manuscripts in India and to give suggestions to transcribe these manuscripts easily, effortlessly and expeditiously. Design/methodology/approach: The study is based on the analytical study of the literature available on global efforts in respect of documentation, preservation, conservation and digitization of manuscripts with special emphasis on the efforts of "namami" (acronym for National Manuscript Mission) for Indian manuscripts. Findings: Meticulous analysis of literature and case studies give an overview of the diverse practices of public participation/crowd collaboration to transcribe and tagging of the rare and old historical documents around the globe. However, Indian libraries are far behind in adopting such practices. Practical implications: India has a very rich cultural, educational and research heritage preserved in the form of manuscripts. These thousands of manuscripts are significant source of knowledge base for many researchers, however, despite their heritage value, these remain inaccessible to the researchers because of their being scattered and unpublished form. Moreover, even the digitized manuscripts remain difficult to use by the researchers because of immense linguistic diversity and scripts. Documentation and digitization of these manuscripts will not only preserve the invaluable heritage of India but also will enable their easy and vast access by the researchers globally. With the rapid growth in digital information and web-based technology, galleries, libraries, archives and museums (GLAM) around the world encourage and engage public participation in various digitization projects to enrich and enhance their digital collections and place them on the web. However, Indian GLAM still refrains to accept and adopt such practices. Thus this paper will encourage and motivate the Indian GLAM to expedite their digitization and uploading them on web for tagging and transcribing. Originality/value: This is an original paper and has great implementation value. During the study enormous literature was available on digitization of Indian manuscripts. However, not even a single study could be found on tagging and transcription of these manuscripts, specifically crowd contribution in this area. Hence, the paper, by presenting the evidences of crowd participation for the tagging and transcription of manuscripts globally, proposes the Indian GLAM to exploit the benefits of this practice for Indian manuscripts also in order to expedite the tagging process to enhance their usage.